2014
DOI: 10.1002/ijc.28830
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells detection has independent prognostic impact in high-risk non-muscle invasive bladder cancer

Abstract: High-risk non-muscle invasive bladder cancer (NMIBC) progresses to metastatic disease in 10-15% of cases, suggesting that micrometastases may be present at first diagnosis. The prediction of risks of progression relies upon EORTC scoring systems, based on clinical and pathological parameters, which do not accurately identify which patients will progress. Aim of the study was to investigate whether the presence of CTC may improve prognostication in a large population of patients with Stage I bladder cancer who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 22 publications
1
66
0
Order By: Relevance
“…Promising studies demonstrating signifi cant correlations between CTC counts and metastatic relapse have been observed in other tumor entities, such as colorectal cancer ( 8 ), bladder cancer ( 45,46 ), liver cancer ( 47 ), and esophageal cancer ( 48 ). Taken together, larger cohorts need to be analyzed using more sensitive CTC assays to further explore the clinical relevance of CTCs in nonmetastatic cancer patients.…”
Section: Ctcsmentioning
confidence: 99%
“…Promising studies demonstrating signifi cant correlations between CTC counts and metastatic relapse have been observed in other tumor entities, such as colorectal cancer ( 8 ), bladder cancer ( 45,46 ), liver cancer ( 47 ), and esophageal cancer ( 48 ). Taken together, larger cohorts need to be analyzed using more sensitive CTC assays to further explore the clinical relevance of CTCs in nonmetastatic cancer patients.…”
Section: Ctcsmentioning
confidence: 99%
“…We thus come back to wonder about the accuracy of considering these forms as early cancers. More recently in a larger and homogeneous population of high-risk non-muscle-invasive bladder cancer patients, we demonstrated that the presence of at least one CTC is a strong predictor of progression, defined as an increase in T stage to T2 or greater or lymph node (N+) disease or distant metastasis (M1), according to international guidelines [14]. Our thought are that these tumors are understaged at the time of diagnosis; in this context, we propose that the American Joint Committee on Cancer category cM0(i+), recently included for breast cancer, might be appropriate for bladder cancer staging as well.…”
Section: Might Ctcs Have a Role In Early Bladder Cancer Management?mentioning
confidence: 99%
“…55,56 It has been reported that CTCs have been detected in localized, high-risk nonmuscle-invasive, and metastatic bladder cancer, and that CTCs have potential prognostic value. [56][57][58][59] In the current study, we applied an integrated magnetic pre-enrichment and multiparameter flow cytometric analysis, a novel method that we recently developed.…”
Section: Discussionmentioning
confidence: 99%